2015
DOI: 10.3390/nu7075217
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline Supplementation Improves Organ Perfusion and Arginine Availability under Conditions with Enhanced Arginase Activity

Abstract: Enhanced arginase-induced arginine consumption is believed to play a key role in the pathogenesis of sickle cell disease-induced end organ failure. Enhancement of arginine availability with l-arginine supplementation exhibited less consistent results; however, l-citrulline, the precursor of l-arginine, may be a promising alternative. In this study, we determined the effects of l-citrulline compared to l-arginine supplementation on arginine-nitric oxide (NO) metabolism, arginine availability and microcirculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 60 publications
1
36
2
Order By: Relevance
“…In total, 55 Ϯ 2% and 53 Ϯ 2% of the ingested protein became available in the circulation during the 5-h postprandial period in the PRO and PRONO3 groups, respectively. Despite previous reports that dietary strategies augmenting NO metabolism may alter gut and organ tissue perfusion (47,56), the greater plasma NO 2 Ϫ availability in the PRONO3 group did not modulate dietary protein digestion, amino acid absorption, or the amount of protein-derived amino acids that became available within the circulation after the ingestion of 20 g of protein in these older, type 2 diabetes patients.…”
Section: E330 Dietary Nitrate Co-ingestion and Muscle Protein Synthesiscontrasting
confidence: 82%
“…In total, 55 Ϯ 2% and 53 Ϯ 2% of the ingested protein became available in the circulation during the 5-h postprandial period in the PRO and PRONO3 groups, respectively. Despite previous reports that dietary strategies augmenting NO metabolism may alter gut and organ tissue perfusion (47,56), the greater plasma NO 2 Ϫ availability in the PRONO3 group did not modulate dietary protein digestion, amino acid absorption, or the amount of protein-derived amino acids that became available within the circulation after the ingestion of 20 g of protein in these older, type 2 diabetes patients.…”
Section: E330 Dietary Nitrate Co-ingestion and Muscle Protein Synthesiscontrasting
confidence: 82%
“…; Wijnands et al. ). This intervention resulted in a small but significant rise of MAP to 108% of control values (9 ± 2.5 mmHg increase, P = 0.007; Fig.…”
Section: Resultsmentioning
confidence: 98%
“…When plasma arginine was depleted acutely by ARG1 bolus injection, the arginine‐availability index dropped to ~25% of the original (Wijnands et al. ). In the present study, a similar intervention caused blood pressure to increase (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, data suggest that oral supplementation of citrulline may be more efficient than oral arginine supplementation during inflammatory conditions 153 . Citrulline also increases plasma arginine levels in SCD 154 , 155 . Interestingly, in a pharmacokinetics study, we found that 10 g of oral glutamine significantly increased both glutamine and arginine bioavailability in patients with SCD at risk for pulmonary hypertension within 4 hours, 150 while glutamine‐enriched enteral nutrition (EN) improved arginine bioavailability in patients with multiple trauma 156 .…”
Section: Methods Of Providing Conditionally Essential Amino Acidsmentioning
confidence: 99%